Applying the Lean Benchmarking method at a metalworking company - Ribeiro do Valle, Anna Claudia; Dal Forno, Ana Julia; Ferrari Tubino, Dalvio; Avila, João Paulo; Augusto Pereira, Fernando (Revista Gestão da Produção Operações e Sistemas, 2008)
The essence of lean manufacturing is to add value and eliminate waste. Companies are not always able to obtain these benefits. The Lean Benchmarking method (BME Benchmarking Enxuto) was developed to diagnose whether companies have the prerequisites needed to implement Toyota Production System techniques and to achieve satisfactory results. The BME method consists of training a multidisciplinary team and applying 37 measurements, divided into practices and performances about demand, product, production control planning and factory floor areas. This article briefly explains this method and illustrates its application in a diagnosis of a large-sized company, a manufacturer of booths, awnings and agricultural platforms, showing how the method can guide the discussion for planning initiatives on how to implement lean manufacturing. Key-words: Benchmarking, Lean Manufacturing, Production Systems.